Perancangan UI/UX pada Website Momsky dengan Metode User Centered Design - Philips Lyionick Corint; Hannie Hannie; Nina Sulistiyowati (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
This research investigates the UI/UX design of the Momsky website employing the User-Centered Design (UCD) methodology to address challenges associated with manual ordering systems, which lead to order inaccuracies, extended customer queues, and communication gaps. The study's objective is to develop a refined website prototype that enhances user usability and overall experience. The UCD approach was systematically applied through five core stages: planning the user-centered process, specifying the context of use, defining user requirements, producing design solutions, and evaluating the design against user requirements. The design and prototyping phases were executed using Figma, yielding wireframes and interactive prototypes for user testing. System evaluation was conducted using the System Usability Scale (SUS) and the User Experience Questionnaire (UEQ). The SUS evaluation, involving 80 respondents, yielded an average score of 76.84, classifying the prototype as acceptable with good usability. Concurrently, the UEQ analysis demonstrated positive user perceptions across key aspects, notably attractiveness, perspicuity, and efficiency, indicating a visually appealing, comprehensible, and effective interface. Consequently, the developed Momsky website prototype effectively mitigates the issues of manual ordering and elevates the user experience. The findings are posited to serve as a foundational basis for the subsequent implementation of the Momsky online ordering system.